FACTORS AFFECTING CAPITAL EXPENDITURE ALLOCATION IN CENTRAL JAVA PROVINCE GOVERNMENT - Linda Ayu Oktoriza; Amerti Irvin Widowati; Surjawati - (Universitas Dian Nuswantoro, 2022)
ABSTRACTDuring the old government, Indonesia used a centralized system, where everything was decided and determined by the central government. Meanwhile, during the Reformation period, a regional autonomy system was implemented where the regions had the right to regulate their own regions with certain limitations. This study purposes to know the factors that affect the Capital Expenditure allocation in the Government of Central Java Province. This research was conducted because there were inconsistent results from previous studies.The data used are secondary data using the period 2017 - 2020 in the district / city in Central Java. Where there are 29 Regencies and 6 Cities. The number of observations was 140 observations from 35 counties / cities observed over 4 periods. Based on the title, background, and problem formulation, the data analysis technique used is multiple linear regression analysis which purposes to measure the strength of the linear association between two or more variables.The results showed that the General Allocation Fund had a significant positive effect on capital expenditure, the Special Allocation Fund had a significant positive influence on capital expenditure, Regional Original Revenue had a significant positive influence on capital expenditure and Gross Regional Domestic Revenue had no influence on capital expenditure.Keywords: General Allocation Fund (GAF); Regional Original Revenue (ROR); Special Allocation Fund (SAF); Gross Regional Domestic Revenue (GRDP); Capital Expenditure